2017
DOI: 10.3390/rs9020178
|View full text |Cite
|
Sign up to set email alerts
|

A Radiometric Uncertainty Tool for the Sentinel 2 Mission

Abstract: Abstract:In the framework of the European Copernicus programme, the European Space Agency (ESA) has launched the Sentinel-2 (S2) Earth Observation (EO) mission which provides optical high spatial resolution imagery over land and coastal areas. As part of this mission, a tool (named S2-RUT, from Sentinel-2 Radiometric Uncertainty Tool) has been developed. The tool estimates the radiometric uncertainty associated with each pixel in the top-of-atmosphere (TOA) reflectance factor images provided by ESA. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…A state-of-the-art synthetic dataset of R rs and at-sensor reflectances for various sensor configurations with coincident measurements of associated IOPs and optical constituent concentrations was developed using novel techniques suited to high biomass, complex optical systems and cyanobacteria dominated waters. The parameterization of the RTM describing the synthetic dataset utilizes our most current understanding of optical properties and relationships related to eutrophic and cyanobacteria dominated waters and includes four prominent novel aspects: 1) two-layered, FIGURE 13 | SNR for water-leaving radiance (L w ) for S2-MSI developed using the ESA Sentinel 2 radiometric uncertainty tool (Gorroño et al, 2017; for the OWTs defined in this study. The black, red, and blue dashed lines represent the theoretical research, validation, and calibration limits described in Kudela et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…A state-of-the-art synthetic dataset of R rs and at-sensor reflectances for various sensor configurations with coincident measurements of associated IOPs and optical constituent concentrations was developed using novel techniques suited to high biomass, complex optical systems and cyanobacteria dominated waters. The parameterization of the RTM describing the synthetic dataset utilizes our most current understanding of optical properties and relationships related to eutrophic and cyanobacteria dominated waters and includes four prominent novel aspects: 1) two-layered, FIGURE 13 | SNR for water-leaving radiance (L w ) for S2-MSI developed using the ESA Sentinel 2 radiometric uncertainty tool (Gorroño et al, 2017; for the OWTs defined in this study. The black, red, and blue dashed lines represent the theoretical research, validation, and calibration limits described in Kudela et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…The Sentinel-2 sensor has low radiometric calibration uncertainty that makes the radiance of the images to produce reliable results. Gorroño, et al [45] and Gorroño, et al [46] reported radiometric uncertainty ranging from 0.03 to 0.4% for Sentinel-2 images. These values are comparable to other sensors such as the Landsat-8 [45] and thus, Sentinel-2 images have the potential to produce highly accurate information to support different applications.…”
Section: Properties Of Sentinel-2 Datamentioning
confidence: 98%
“…Generally, the outcomes of such comparisons are to compute inter-sensor differences or "biases" in given conditions, but, without uncertainty information, it is difficult to form any definitive quantitative conclusion whether these observed differences indicate the sensors are achieving their specified performance. Efforts are therefore on-going to develop the techniques to facilitate the evaluation and dissemination of satellite sensor uncertainty information [5], with some missions now able to provide this (e.g., Sentinel-2 [6,7]). Sensor uncertainty information is also available for both SLSTR L1 and L2 SST products [3,8].…”
Section: Introductionmentioning
confidence: 99%